PENGEMBANGAN MODUL PEMBELAJARAN MATEMATIKA BERBASIS PENEMUAN TERBIMBING UNTUK MATERI GEOMETRI KELAS X SMAN 2 RANAH PESISIR - Putra, Riki Jaseka (STKIP PGRI Sumbar, 2014)
The background of the research is base on module that used by the teacher inlearning process still low in creasing studentâs motivation and contructionstudentâs knowledge. It means that, module as source in learning is not be able tocreate interesting activity in learning process. It needs to develope teachingmaterial like module base on discovery learning. The research is focus onmaterial about geometry. The purpose of this research is creating module in mathlearning base on discovery learning in validly and practically in geometry subjectat senior high school 2 Ranah Pesisir. In designing this research, researcher used4-D. There are three steps have done. Those are define, design, and develop. Theresult showed that module in math learning base on discovery learning was validwhich precentage 85%. It was also practice which precentage 84%. Thus,module that used base on indicators such as benefit, easy to understand, andinteresting.